Quartz pellets for silicon alloy production and preparation method thereof
By preparing quartz pellets with high explosion resistance, large specific surface area and high internal porosity, the problems of small contact area and insufficient reaction in the production of silicon-based alloys are solved, and efficient, stable and controllable silicon-based alloy production is achieved, reducing power consumption and production costs, and reducing microsilicon dust emissions.
Patent Information
- Application Number
- CN202410897700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-07-05
AI Technical Summary
In the production of silicon alloys, there is a small contact area between the raw silica and the reducing agent and insufficient reaction, resulting in low explosion resistance, high power consumption, surface bonding, large thermal energy loss, low silicon dioxide utilization rate, serious microsilicon dust emissions, low degree of automation, and high production costs.
A preparation method is used to prepare quartz pellets, including crushing silica blocks into quartz powder, adding 3-5% binder and 8-10% magnetized purified water, and after stirring and pressing the ball, quartz pellets with a diameter of 36-52mm and a height of 32-48mm were obtained. The pellet has high explosion resistance, large specific surface area and high internal porosity. It can stably sinter at high temperatures and reduce the risk of pulverization and blockage.
Quartz pellets are sintered under high temperature conditions without crushing or powdering, keep the furnace condition stable, reduce energy and material losses, improve the efficiency of reduction reactions, reduce power consumption, and improve the utilization rate of silica, realize the efficient, stable and controllable production of silicon alloys, reduce production costs, and reduce microsilicon dust emissions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon series alloy production, and in particular to quartz pellets used for silicon series alloy production and a preparation method thereof. Background Art
[0002] In order to solve the huge crisis and challenge of global warming, major countries in the world have already regarded the development of a low-carbon economy as a prerequisite for economic construction and development at present and for a long time in the future. As the world's largest producer of silicon-based alloys, my country has currently achieved an annual production capacity of 6 million tons of ferrosilicon and 3 million tons of industrial silicon. With the high-quality development of the manufacturing and steel industries, the market needs a large amount of special steel. At the same time, hazardous wastes generated in industrial production, such as microsilicon powder produced in the production of silicon-chromium alloys, contain hexavalent chromium ions, which are dangerous carcinogens. Therefore, it is necessary to cold-press the microsilicon powder and silica powder into pellets for secondary use, and then reduce all the chromium elements in them into ferroalloy products for recycling.
[0003] However, the following problems are common in the production of products such as ferrosilicon and industrial silicon: (1) The contact area between the raw material silica and the reducing agent in the production of silicon-based alloys is small, the reaction is not sufficient, and the explosion resistance is less than 90%. Silica with a diameter of 40-200 mm will explode at 1500°C, producing powder particles with a particle size of ≤10 mm, causing unstable furnace operation, resulting in material surface adhesion, increased power consumption, and severe ignition, causing a large amount of reducing gas to overflow, large heat energy loss, high material surface temperature, serious heat loss in the copper tiles of the furnace equipment and the cooling system, and frequent thermal shutdowns, which in turn leads to increased power consumption; (2) The utilization rate of silicon dioxide is 70-80% for the production of 1 t of industrial silicon, and the consumption of silica and carbonaceous reducing agents is large. Moreover, the production of 1 ton of industrial silicon will generate 400-600 kg of micro-silicon dust. In severe cases, the silicon alloy thermal electric furnace will be shut down and the furnace needs to be manually rammed and rebuilt. The degree of automation is low and the production cost is high. (3) In theory, the production of 1 ton of industrial silicon consumes 6770 degrees of electricity. However, in actual silica smelting, silica exists in the form of α-quartz at room temperature. When the temperature rises, α-quartz will undergo a series of crystal transformations, resulting in a power consumption of up to 13,000 degrees, which is costly. (4) The thermal electric furnace cannot be fully enclosed, resulting in the exhaust gas from the furnace containing a large amount of carbon monoxide that cannot be recycled, and zero carbon emissions cannot be achieved. In addition, each ton of industrial silicon will generate 1700-2300m 3 The CO content of the furnace gas is about 60-80%, which cannot be recycled and does not meet the development requirements of zero carbon emissions in the ferroalloy industry. (5) Due to the use of block silica in the production process, the electric furnace is always in an unstable operating state and cannot be digitally produced through AI control. Summary of the invention
[0004] The present invention provides a quartz pellet for silicon alloy production and a preparation method thereof, the purpose of which is to prepare a quartz pellet with high reducibility, high explosion resistance, high specific surface area, high intra-pellet porosity and low reduction starting temperature, to ensure that the quartz pellet is not broken or pulverized during sintering under high temperature conditions, does not block the ore-fired furnace, keeps the furnace condition stable, reduces the loss of energy and materials, and increases the specific surface area and reduction efficiency of the reduction reaction.
[0005] To achieve its purpose, the present invention adopts the following technical solution:
[0006] A method for preparing quartz pellets for silicon alloy production comprises the following steps:
[0007] Step 1: crushing and grinding silica blocks to obtain quartz powder;
[0008] Step 2: Add 3-5% by weight of a binder to the quartz powder obtained in step 1 and mix well to obtain a quartz powder mixture;
[0009] Step 3: adding 8-10% by weight of magnetized pure water to the quartz powder mixture obtained in step 2, and stirring to obtain a pellet blank;
[0010] Step 4: The pellets obtained in step 3 are sent to a pellet press to be pressed and sieved to obtain wet balls and undersize materials, and the undersize materials are returned to step 3 for repeated use;
[0011] Step 5: The wet ball obtained in step 4 is naturally air-dried to obtain a finished quartz ball with a diameter of D = 36-52mm and a height of H = 32-48mm.
[0012] Furthermore, in terms of weight percentage, the silica block in step 1 contains SiO2>99%, Al2O3<0.3%, Fe2O3<0.3%, and the particle size of the silica block is ≤5mm.
[0013] Furthermore, in step one, the grinding is performed using a vertical grinding mill.
[0014] Furthermore, in step 1, the particle size of the quartz powder is 150-300 mesh.
[0015] Furthermore, in step 2, the binder contains, by weight percentage, 0.5-1.5% pregelatinized corn starch, 0.5-1.5% pregelatinized cassava starch, 0.1-0.8% polyvinyl alcohol, 0.2-1% carboxymethyl cellulose, 0.2-1.2% sodium carboxypropyl methyl cellulose, 0.5-2.5% sodium hydroxide and 1-5.5% instant sodium silicate pentahydrate; wherein the pregelatinization temperature of the pregelatinized corn starch and the pregelatinized cassava starch is 65-75°C.
[0016] Furthermore, when the air humidity is greater than 50%, 5-10% by weight of microsilica powder is used to replace pregelatinized corn starch and pregelatinized cassava starch.
[0017] Furthermore, the mixing operation in step 2 adopts a drum-type stirring mixer.
[0018] Furthermore, the mixing operation in step three adopts a wheel mixer.
[0019] Furthermore, in step 4, the ball press machine adopts a double-roller high-power ball press machine; the screening operation adopts a roller screen with a mesh size ≥ 20 mm.
[0020] The quartz pellets prepared by the above preparation method contain SiO2>96%, Al2O3<0.8%, and Fe2O3<0.8% by weight.
[0021] The beneficial effects of the present invention are as follows:
[0022] 1. The quartz pellets prepared by the preparation method of the present invention have a diameter of about 36 mm, a height of about 32 mm, and a shape approximately spherical. When used in the production of silicon-based alloys, the quartz pellets and the carbonaceous reducing agent fall freely from the material tube and enter the surface of the ore-fired furnace. The large balls are quartz pellets, and the small balls are carbonaceous reducing agent pellets. The large and small spheres are tightly packed, the material distribution is uniform, the porosity is greater than 20%, and no deflagration or explosion occurs at a furnace temperature below 1700°C, and the safety is high.
[0023] 2. When preparing the quartz pellets of the present invention, by adding a binder, under the coupling, mineralization and pore-increasing effects of the binder, the quartz powder produces a low-melting-point silica sol liquid phase at 1000°C, and the formed quartz pellets can withstand high temperatures of 1600-1700°C, and have the effect of mineralization and reduction at high temperatures. After the quartz pellets are naturally air-dried, they have high explosion resistance (explosion resistance>99.5%) at a high temperature of 1650°C in a mineral heat electric furnace, and no quartz powder particles are produced, forming a good reducing atmosphere, thereby efficiently, stably and controllably producing silicon-based alloys. The thermal strength of the quartz pellets at high temperatures is greater than 1000N. They will not be crushed, will not produce powder particles with a particle size of ≤10mm, and will not block the channel of the reducing gas, so that the reducing gas can rise smoothly, react on the carbonaceous reducing agent pellets, and undergo a disproportionate reaction in the internal gaps of the quartz pellets to condense and generate Si, etc. The Si liquid falls freely to the metal pool at the bottom of the furnace, without piercing fire, and the heat energy is concentrated below the material surface. The material surface is not bonded, and no manual tamping is required. The degree of automation is high, and the fully closed operation of the ore-fired electric furnace can be achieved. The reducing gas is highly adsorbed by the carbonaceous reducing agent, and the heat energy is fully exchanged, which fully reduces SiO2, greatly reducing the overflow of SiO, and the material surface temperature is 50% lower than normal.
[0024] 3. The quartz pellets prepared by the preparation method provided by the present invention have a large specific surface area. The silica is crushed and finely ground into quartz powder with a particle size of 200 mesh, i.e. 0.0074 cm. Assuming that the quartz powder has no voids, the specific surface area is approximately:
[0025] S=k / ρd
[0026] ρ is the density of quartz powder. Quartz becomes cristobalite above 1500℃, and its density is 2.36g / cm 2 ; k = 9; because the shape of quartz powder is hexahedral, d is the average particle size of quartz powder, d = 0.0074cm; calculation shows that the specific surface area of quartz powder above 1500℃ is S = 9 / 2.36×0.0074cm≈515cm 2 / g; At high temperatures, silica breaks into small pieces with an average size of 25-30 mm; Above 1500°C, the specific surface area of silica is S = 9 / 2.36×2.5 ≈1.5 cm 2 / g; the weight of a quartz pellet is about 29.4g, and the weight of a silica is about 50g, so S 石英球团 / S 硅石 =515 / 1.5≈343;
[0027] Therefore, assuming that there are no voids in the quartz pellets, the specific surface area of the quartz pellets at high temperatures is about 343 times that of silica. The large specific surface area allows for sufficient contact with the carbon reducing agent and a large area, and has a strong ability to adsorb reducing gases. Therefore, the reduction reaction ability of the quartz pellets is at least 343 times that of silica.
[0028] 4. The preparation method of the present invention is to add 3-5% of a binder to quartz powder, produce quartz pellets under high pressure or strong pressure, and after natural air drying at room temperature, the porosity of the quartz pellets is measured to be 28-29%. After calcination at 1600°C, the porosity is about 42%, and the volume increases by 17%, while the porosity of traditional silica is only 2.78% at high temperature. As the temperature continues to rise to 1650°C, the specific surface area of quartz pellets increases geometrically compared with silica. Therefore, in a thermal electric furnace, under a silicon dioxide reducing atmosphere, a large amount of reducing gas will enter the internal pores of the pellets to carry out a microcirculation reaction. Under the condition of high porosity, the specific surface area is further increased, the gas and ions in the pellets will be adsorbed, the gas is not easy to overflow, and the heat energy will be gathered inside and outside, while the heat energy of traditional silica is only gathered outside, so the quartz pellets can be effectively conducted from outside to inside, not only the heat energy loss is small, but also the heat energy will promote the reduction reaction to be carried out more fully. In addition, the temperature of the charge surface of the smelting furnace is reduced by 200-300℃, making the furnace body conductive, water circulation, and furnace shell systems less likely to burn, resulting in fewer thermal shutdowns, less power consumption, and extended equipment operation time.
[0029] 5. Referring to the article entitled "Comparative Study on the Effects of NaCl and NaOH on Quartz Crystalline Transformation", combined with the preparation processes of different silicon-containing alloys, it can be seen that if alkali metal ions participate in the reaction during smelting, the reduction temperature can be reduced. Therefore, the binder used in the present invention contains 1-1.5% sodium hydroxide as a mineralizer. At 1200°C, the active Na + It has strong expansion agent properties, fast migration speed, and accelerates the reaction process; and Na + It forms a variety of metastable systems with SiO2, significantly improving the degree of freedom of the system, increasing the reactivity of crystalline SiO2, causing quartz powder lattice distortion, increasing the number of SiO-O bond breaks, forming more lattice defects, accelerating the decomposition of α-quartz, reconstructing the nucleation of α-cristobalite, and causing the temperature of SiO2 crystal transformation to form cristobalite phase to decrease. X-ray analysis shows that at 1200℃, Na + When the content is 1-1.5%, the conversion rate of cristobalite is 85-92%. The starting temperature of cristobalite generated by conventional silica smelting is above 1470℃, while the starting temperature of quartz pellet reduction is 1200-1400℃, or even lower. Therefore, compared with the traditional silica reduction temperature of 1580℃, the starting reduction temperature is greatly reduced. The lower the starting reduction temperature, the less heat energy is needed, which creates new material conditions for carbon reduction of silicon dioxide in the thermal electric furnace, making it stable in operation, with controllable reduction atmosphere, less equipment maintenance and thermal shutdown, and from passive participation in the reaction to artificial AI control, active participation in the reaction, lowering the starting reduction temperature, and reducing the heat energy required for the reduction reaction. Calculations based on thermodynamic theory show that the electricity consumption required for reducing silicon with the quartz pellets produced by the present invention is reduced by about 15%, and the overall electricity consumption is controlled below 10,000 degrees, which reduces heat energy loss and improves heat energy utilization, ultimately achieving energy savings of 20-30%, and a silicon dioxide utilization efficiency of about 95% (an increase of 30%), thus realizing the vision and goal of environmentally friendly and zero-carbon emission ferroalloy production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a flow chart of the preparation method of the present invention;
[0031] Figure 2 This is a real picture of the cold ball in Example 1 of the present invention;
[0032] Figure 3 This is a real picture of the hot ball in Example 1 of the present invention;
[0033] Figure 4 The uncalcined original ball in Example 1 of the present invention;
[0034] Figure 5 The quartz pellets are calcined at 1650° C. in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with embodiments:
[0036] In the following embodiments, the percentages (%) involved are all weight percentages. The vertical grinding mill used for grinding has an output of 8-50t / h. The drum-type stirring mixer used for mixing has an output of 6-12m³ / h and a power of 4-7.5kw. The wheel-rolling mixer used for stirring has a mixing drum diameter of 1.2-2.2m, a rotation speed of 10-15r / min, a stirring frequency of 3-6min / time, and a power of 5.5-30kw. The double-roller strong ball press used for ball pressing has a roller diameter of 360-520mm, a motor power of 7.5-18KW, a designed output of 3-8t / h, and a spindle speed of 12-15r / min.
[0037] Example 1
[0038] The method for preparing cold-pressed quartz powder pellets for producing 75# ferrosilicon comprises the following steps:
[0039] Step 1: crush and grind silica blocks with a particle size of ≤5mm to obtain quartz powder with a particle size of 200 mesh; wherein the silica blocks contain SiO2: 99.5%, Al2O3: 0.2%, and Fe2O3: 0.2%; the grinding is carried out using a 800-type vertical grinding mill with an output of 8t / h;
[0040] Step 2: Add 3% of a binder to the quartz powder obtained in step 1 and feed it into a mixer for mixing to obtain a quartz powder mixture; wherein the binder contains 1% of pregelatinized corn starch, 1% of pregelatinized cassava starch, 0.4% of polyvinyl alcohol, 0.3% of carboxymethyl cellulose, 0.3% of sodium carboxypropyl methylcellulose, 0.8% of sodium hydroxide and 1.2% of instant sodium silicate pentahydrate; the pregelatinization temperature of the pregelatinized corn starch and the pregelatinized cassava starch is 65°C; the mixer is a drum-type stirring mixer with a yield of 12m³ / h and a power of 6kw;
[0041] Step 3: Add 8% of magnetized pure water to the quartz powder mixture obtained in step 2, and stir to obtain a pellet blank; the mixer used for stirring is a wheel mixer, the mixing drum diameter is 2.2m, the speed is 15r / min, the stirring frequency is 3min / time, and the power is 15kw;
[0042] Step 4: Send the pellets obtained in step 3 to a 360-type double-roller high-pressure ball press to press and sieve to obtain wet balls and undersize tailings, and the undersize tailings are returned to step 3 for repeated use; the ball press has a roller diameter of 360 mm, a motor power of 7.5 KW, a designed output of 8 t / h, and a spindle speed of 15 r / min.
[0043] Step 5: The wet ball obtained in step 4 is naturally air-dried to obtain a quartz ball with a diameter of 36 mm and a height of 38 mm; Figure 4 As shown; the quartz pellets contain SiO2: 97%, Al2O3: 0.7%, and Fe2O3: 0.6%.
[0044] The strength of the wet ball, original ball and hot ball of the quartz pellets and the explosion resistance of the hot ball were tested respectively, and the results are as follows:
[0045] (1) Wet ball: The quartz ball in step 4 is wetted and dropped freely from a height of 2 m. After repeating the experiment 5 times in a row, the ball remains intact and does not break;
[0046] (2) Original ball: After the wet ball is naturally air-dried for 5-7 days, the original quartz ball is obtained. Figure 2 As shown, the original ball is dropped freely from a height of 3-4m, and the experiment is repeated 5 times in succession, and the ball remains intact and does not break. The strength tested by the HLD hand-cranked tensile and compression testing machine of Edberg is 1000N;
[0047] (3) Hot ball: Figure 3 As shown in the figure, the GWL-1700XL high temperature muffle furnace is first heated to 600℃, and then 45 quartz pellets are placed in the furnace and kept at a constant temperature for 30 minutes, and then gradually heated to 1650℃, and calcined at 1650℃ for 1h. During the calcination process, all the pellets do not break or explode; after the calcination is completed, the furnace is cooled to 600℃ and the pellets are taken out. All 45 pellets remain intact, indicating that their explosion resistance is 100%; among them, the uncalcined single pellet original ball is as follows Figure 4 As shown in Figure 2, the quartz pellets calcined at 1650℃ are Figure 5 As shown, it can be seen that the pellets remain intact despite the increase in volume. The strength tested by the HLD hand-cranked tensile and compression testing machine is 1000N.
[0048] The cost and various indexes of 75# ferrosilicon smelting by using the quartz pellets of the present invention are compared with those of traditional silica production as shown in Table 2:
[0049]
[0050] Example 2
[0051] A method for preparing quartz pellets for producing industrial silicon of grade 2201 and above and high-purity ferrosilicon comprises the following steps:
[0052] Step 1: crush and grind silica blocks with a particle size of ≤5mm to obtain quartz powder with a particle size of 300 mesh; wherein the silica blocks contain SiO2: 99.5%, Al2O3: 0.2%, and Fe2O3: 0.2%; the grinding is carried out using a 800-type vertical grinding mill with an output of 50t / h;
[0053] Step 2: Add 3% of a binder to the quartz powder obtained in step 1 and feed the mixture into a mixer for mixing to obtain a quartz powder mixture; wherein the binder contains 1% of pregelatinized corn starch, 1% of pregelatinized cassava starch, 0.4% of polyvinyl alcohol, 0.3% of carboxymethyl cellulose, 0.3% of sodium carboxypropyl methylcellulose, 0.8% of sodium hydroxide and 1% of instant sodium silicate pentahydrate; the pregelatinization temperature of the pregelatinized corn starch and the pregelatinized cassava starch is 75°C; the mixer is a drum-type stirring mixer with a yield of 8m³ / h and a power of 4kw;
[0054] Step 3: Add 8% of magnetized pure water to the quartz powder mixture obtained in step 2, and stir to obtain a pellet blank; the mixer used for stirring is a wheel mixer, the mixing drum diameter is 1.2m, the speed is 15r / min, the stirring frequency is 6min / time, and the power is 11kw;
[0055] Step 4: Send the pellets obtained in step 3 to a 360-type double-roller high-pressure ball press for ball pressing and sieving to obtain wet balls and undersize tailings, and the undersize tailings are returned to step 3 for repeated use; the ball press has a roller diameter of 360 mm, a motor power of 15 KW, a designed output of 3 t / h, and a spindle speed of 12 r / min.
[0056] Step 5: Naturally air-dry the wet ball obtained in step 4 to obtain a quartz pellet with a diameter of 36 mm and a height of 32 mm; the quartz pellet contains SiO2: 98%, Al2O3: 0.4%, and Fe2O3: 0.5%.
[0057] First, the GWL-1700XL high-temperature muffle furnace was heated to 600°C, and then 210 quartz pellets were placed in the furnace and kept at a constant temperature for 30 minutes before being heated to 1650°C. After calcining at 1650°C, 209 pellets did not break or explode. After the furnace was cooled to 600°C, the pellets were taken out, 209 remained intact, and only one pellet had a slight crack, indicating that its explosion resistance was 99.52%.
[0058] Compared with the traditional production using silica, the use of the quartz pellets of the present invention for industrial silicon smelting has the following beneficial effects: (1) the power consumption is reduced from 13,000 degrees to below 10,000 degrees, reducing the power consumption by about 23%; (2) the reduction rate of SiO2 is improved, and the utilization rate of SiO2 is increased from 75% to 93%; (3) the silica consumption is controlled below 2.3 tons; (4) automatic control reduces manual input. The consumption of other materials (carbon electrodes, petroleum coke, wood blocks, silicon coal, etc.) used in the production of silicon-based alloys is reduced by 20% compared with the use of silica, the overall production cost is reduced by more than 20%, and the emission of microsilicon powder is reduced by about 60%.
[0059] Example 3
[0060] Since the hazardous solid waste generated in the production of silicon-chromium alloy, such as microsilica powder, contains hexavalent chromium ions, which are dangerous carcinogens, it is necessary to use microsilica powder as a binder component and cold-press it with silica blocks into pellets for secondary use in the furnace, and then reduce all the chromium elements in it into ferroalloy products for recycling. The preparation method of the quartz pellets includes the following steps:
[0061] Step 1: crush and grind silica blocks with a particle size of ≤5mm to obtain quartz powder with a particle size of 150 mesh; wherein the silica blocks contain SiO2: 99.5%, Al2O3: 0.2%, and Fe2O3: 0.25%; the grinding is carried out using a 800-type vertical grinding mill with an output of 8t / h;
[0062] Step 2: Add 5% of a binder to the quartz powder obtained in step 1 and feed it into a mixer for mixing to obtain a quartz powder mixture; wherein the binder contains 0.4% of polyvinyl alcohol, 0.3% of carboxymethyl cellulose, 0.3% of sodium carboxypropyl methyl cellulose, 1% of sodium hydroxide, 1.5% of instant sodium silicate pentahydrate and 10% of microsilica powder (microsilica powder produced in the production of silicon-chromium alloy is used to replace pregelatinized corn starch and pregelatinized cassava starch); the mixer is a drum-type stirring mixer with a production rate of 6m³ / h and a power of 7.5kw;
[0063] Step 3: Add 10% of magnetized pure water to the quartz powder mixture obtained in step 2, and stir to obtain a pellet blank; the mixer used for stirring is a wheel mixer, the mixing drum diameter is 1.5m, the speed is 10r / min, the stirring frequency is 5min / time, and the power is 20kw;
[0064] Step 4: Send the pellets obtained in step 3 to a 520-type double-roller high-pressure ball press for ball pressing and sieving to obtain wet balls and undersize tailings, and the undersize tailings are returned to step 3 for repeated use; the ball press has a roller diameter of 520 mm, a motor power of 18 KW, a designed output of 6 t / h, and a spindle speed of 13 r / min.
[0065] Step 5: Naturally air-dry the wet ball obtained in step 4 to obtain a quartz pellet with a diameter of 52 mm and a height of 48 mm; the quartz pellet contains SiO2: 97%, Al2O3: 0.7%, and Fe2O3: 0.6%.
[0066] First, the GWL-1700XL high-temperature muffle furnace was heated to 600°C, and then 270 quartz pellets were placed in the furnace and kept at a constant temperature for 30 minutes and then heated to 1650°C. After calcining at 1650°C, the 270 pellets did not crack or explode. After the furnace cooled to 600°C, the pellets were taken out, and 269 remained intact, with only a small amount of slag falling off the edge of one pellet, indicating that its explosion resistance was 99.62%.
[0067] When the quartz pellets of the present invention are used for smelting, compared with the traditional production using silica, the beneficial effects are as follows: (1) the hazardous dust containing hexavalent chromium ions generated by reducing silicon-chromium alloy can be recycled, and no dust is discharged to the outside during the production of silicon-chromium alloy; (2) the power consumption is reduced from 4800 degrees to 4300 degrees, reducing the power consumption by about 10%; (2) the reduction rate of SiO2 is improved, and the utilization rate of SiO2 is increased from 92% to 97%; (3) the silica consumption is controlled below 2.3 tons; (4) automatic control reduces manual input, and the quartz powder pellets used in the production of silicon-based alloys are 10% lower than the consumption of other materials (electrodes, semi-coke, etc.) using silica, and the silica consumption is reduced from 1.04 tons to 0.98 tons, and the overall production cost is reduced by more than 20%.
[0068] Example 4
[0069] A method for preparing cold-pressed quartz powder pellets for producing common ferrosilicon and industrial silicon in humid southern regions with an air humidity of more than 50% comprises the following steps:
[0070] Step 1: crush and grind silica blocks with a particle size of ≤5mm to obtain quartz powder with a particle size of 200 mesh; wherein the silica blocks contain SiO2: 99.5%, Al2O3: 0.25%, Fe2O3: 0.2%; grind using a 800-type vertical grinding mill, with an output of 8t / h;
[0071] Step 2: Add 3% of a binder to the quartz powder obtained in step 1 and send it into a mixer for mixing to obtain a quartz powder mixture; wherein the binder contains 0.4% polyvinyl alcohol, 0.3% carboxymethyl cellulose, 0.3% sodium carboxypropyl methyl cellulose, 1% sodium hydroxide, 1.5% instant sodium silicate pentahydrate and 10% microsilica powder; the mixer is a drum-type stirring mixer with a yield of 6m³ / h and a power of 7.5kw;
[0072] Step 3: Add 10% of magnetized pure water to the quartz powder mixture obtained in step 2, and stir to obtain a pellet blank; the mixer used for stirring is a wheel mixer, the mixing drum diameter is 1.5m, the speed is 10r / min, the stirring frequency is 5min / time, and the power is 20kw;
[0073] Step 4: Send the pellets obtained in step 3 to a 360-type double-roller high-pressure ball press to press and sieve to obtain wet balls and undersize tailings, and the undersize tailings are returned to step 3 for repeated use; the ball press has a roller diameter of 360 mm, a motor power of 7.5 KW, a designed output of 6 t / h, and a spindle speed of 13 r / min.
[0074] Step 5: Naturally air-dry the wet ball obtained in step 4 to obtain a quartz pellet with a diameter of 42 mm and a height of 40 mm; the quartz pellet contains SiO2: 97%, Al2O3: 0.7%, and Fe2O3: 0.4%.
[0075] First, the GWL-1700XL high-temperature muffle furnace was heated to 600°C, and then 200 quartz pellets were placed in the furnace at a constant temperature for 30 minutes and then heated to 1650°C. After calcination at 1650°C, the 200 pellets did not break or explode. After the furnace cooled to 600°C, the pellets were taken out and all 200 pellets remained intact, indicating that their explosion resistance was 100%. Because microsilica powder has ultra-fine particle size, good chemical inertness, high-temperature stability and excellent physical properties, microsilica powder is added to quartz pellets to replace pregelatinized corn starch and pregelatinized cassava starch, which plays a role in moisture-proof and waterproofing, and can also recycle the dangerous dust containing hexavalent chromium ions produced by reducing silicon-chromium alloy.
[0076] It can be seen from Examples 1-4 that the explosion resistance of the quartz pellets prepared by the method of the present invention is greater than 99.5%. When used in the production of silicon-based alloys, the quartz pellets are sintered under high temperature conditions without breaking or pulverizing, and do not clog the ore-fired furnace. The furnace condition is stable, and the pellets made of quartz powder obtained by crushing silica blocks to 200 mesh have the best explosion resistance and reducibility.
Claims
1. A method for preparing quartz pellets for silicon alloy production, characterized in that: The following steps are involved: Step 1: crushing and grinding the silica block to obtain quartz powder with a particle size of 150-300 mesh; Step 2: adding 3-5% by weight of a binder to the quartz powder obtained in step 1 and mixing them to obtain a quartz powder mixture; the binder contains 0.5-1.5% pregelatinized corn starch, 0.5-1.5% pregelatinized cassava starch, 0.1-0.8% polyvinyl alcohol, 0.2-1% carboxymethyl cellulose, 0.2-1.2% sodium carboxypropyl methyl cellulose, 0.5-2.5% sodium hydroxide and 1-5.5% instant sodium silicate pentahydrate; wherein the pregelatinization temperature of the pregelatinized corn starch and the pregelatinized cassava starch is 65-75°C; Step 3: adding 8-10% by weight of magnetized pure water to the quartz powder mixture obtained in step 2, and stirring to obtain a pellet blank; Step 4: The pellets obtained in step 3 are sent to a pellet press to be pressed and sieved to obtain wet balls and undersize materials, and the undersize materials are returned to step 3 for repeated use; Step 5: The wet ball obtained in step 4 is naturally air-dried to obtain a finished quartz ball with a diameter of D = 36-52mm and a height of H = 32-48mm.
2. The method for preparing quartz pellets for silicon alloy production according to claim 1, characterized in that: In terms of weight percentage, the silica block in step 1 contains SiO2>99%, Al2O3<0.3%, Fe2O3<0.3%, and the particle size of the silica block is ≤5mm.
3. The method for preparing quartz pellets for silicon alloy production according to claim 2, characterized in that: The grinding in step 1 is performed using a vertical grinding mill.
4. The method for preparing quartz pellets for silicon alloy production according to claim 3, characterized in that: When the air humidity is greater than 50%, 5-10% by weight of microsilica powder is used to replace pregelatinized corn starch and pregelatinized cassava starch.
5. The method for preparing quartz pellets for silicon alloy production according to any one of claims 1 to 4, characterized in that: The mixing operation in step 2 adopts a drum-type stirring mixer.
6. The method for preparing quartz pellets for silicon alloy production according to any one of claims 1 to 4, characterized in that: The stirring operation in step 3 is performed using a wheel mixer.
7. The method for preparing quartz pellets for silicon alloy production according to any one of claims 1 to 4, characterized in that: The ball press described in step 4 uses a double-roller high-power ball press; the screening operation uses a roller screen with a mesh size ≥ 20 mm.
8. The quartz pellets prepared by the method for preparing quartz pellets for silicon alloy production according to any one of claims 1 to 4 are characterized in that: Calculated by weight percentage, the quartz pellets contain SiO2>96%, Al2O3<0.8%, and Fe2O3<0.8%.
Citation Information
Patent Citations
Quartz pellet for manufacturing high purity ferrosilicon and preparation method of quartz pellet
CN102061380A
Method for improving conversion ratio of alpha-cristobalite crystal form through sodium hydroxide
CN104030295A
Adhesive for preparing silicon smelting waste carbon-containing pellet and preparation method of pellet
CN104140102A